The application of coconut fiber as dissipative silencer - Madlan, Mohd Amran; Ghazali, M. I.; Zaman, Izzuddin; Kasron, Md Zainorin; Ying, T. C. (IOP Publishing, 2017)
Heat ventilation air conditioning system (HVAC) is one of the ducting systems that broadly applied in the building. There are HVAC silencers in the market, however the sound absorptive material commonly used is mineral wool. In this research study, a sound absorptive material made of coconut fiber was tested to identify its performance as a potential replacement of green material for ducting silencer. The experiment was carried out in a testing apparatus that follows the BS EN ISO 11691:2009 standard. Different configurations of sound absorptive material and contents of coconut fiber were investigated in the study. The trend of insertion loss at 1/3 octave frequency was identified where at frequency below 3000Hz, the insertion loss of dissipative silencer is observed high at certain frequency with a very narrow range. At 3000Hz, the insertion loss of 4dB to 6dB is constant until 4000Hz and drops until 5000Hz before it increases again steadily up to 13dB at 10000Hz. A similar trend was observed for different configuration of sound absorptive material. Despite the configuration different, the outcome shows that the insertion loss is increasing with higher content of coconut fiber.